The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2000
DOI: 10.1176/appi.ajp.157.5.781
|View full text |Cite
|
Sign up to set email alerts
|

Visual Perception and Working Memory in Schizotypal Personality Disorder

Abstract: Objective-Patients affected by schizophrenia show deficits in both visual perception and working memory. The authors tested early-stage vision and working memory in subjects with schizotypal personality disorder, which has been biologically associated with schizophrenia.Method-Eleven subjects who met DSM-III-R criteria for schizotypal personality disorder and 12 normal comparison subjects were evaluated. Performance thresholds were obtained for tests of visual discrimination and working memory. Both form and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0
1

Year Published

2002
2002
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 47 publications
(61 reference statements)
4
34
0
1
Order By: Relevance
“…parents, siblings, children) demonstrate deficits on tasks designed to measure working memory function (Park et al 1995a;Callicott et al 2003). In addition, individuals who score high on measures of psychosis proneness and individuals diagnosed with schizotypal personality disorder (Barch et al, unpublished data;Park et al 1995b;Park and McTigue 1997;Farmer et al 2000;Lenzenweger and Gold 2000;Roitman et al 2000;Mitropoulou et al 2002) also display deficits on working memory tasks.…”
Section: Pharmacological Manipulation Of Human Working Memorymentioning
confidence: 99%
“…parents, siblings, children) demonstrate deficits on tasks designed to measure working memory function (Park et al 1995a;Callicott et al 2003). In addition, individuals who score high on measures of psychosis proneness and individuals diagnosed with schizotypal personality disorder (Barch et al, unpublished data;Park et al 1995b;Park and McTigue 1997;Farmer et al 2000;Lenzenweger and Gold 2000;Roitman et al 2000;Mitropoulou et al 2002) also display deficits on working memory tasks.…”
Section: Pharmacological Manipulation Of Human Working Memorymentioning
confidence: 99%
“…Individuals with SPD, for example, show deficits in nonverbal learning, and especially in verbal learning (51), in working memory (52), and in several executive functions, including concept formation, abstraction, and mental flexibility (53). Similarly, relatives of patients who do not have SPD show dysfunction in several cognitive domains, including motor and perceptual-motor ability, short-term memory, working memory, learning and recall, verbal and language skills, sustained attention, and executive function (2).…”
Section: Neuropsychological Deficitsmentioning
confidence: 99%
“…Studies of monozygotic and dizygotic twins pairs discordant for schizophrenia (Cannon et al 2000 ;Glahn et al 2005) indicate that SWM deficits are associated with increased genetic risk for schizophrenia, and it has been suggested that a higher genetic loading for disease-related traits is linked to greater cognitive impairment (Saperstein et al 2006). Impaired spatial memory performance has also been reported in subjects with high levels of schizotypy (Park et al 1995) or schizotypal personality disorder (Farmer et al 2000), and in those with a history of very preterm birth (Narberhaus et al 2009). …”
Section: Introductionmentioning
confidence: 99%